Android-based Geographic Information System for Worship Places in Fakfak Regency - Arridha, Riyadh; Magfirah, Titing; Hayunada, Carlina Dewi; Astuti, Diah (Sinkron : jurnal dan penelitian teknik informatika, 2021)
The rapid development of technology greatly affects people's lives today, one of which in Fakfak City has all been entered by the development of information technology. Fakfak is one of the regencies on the Papua island, the people of Fakfak Regency highly uphold religious values ​​and it is proven by the motto "Satu Tungku Tiga Batu". In Fakfak Regency, one of the the problems faced by some people is the search of worship places that must be done manually, by asking people around, or by looking at a map. In addition, some places of worship have historical values ​​that need to be known by many people. For example, the oldest mosque in Papua and West Papua is in Fakfak Regency. Regarding to this problem, an information system was created that can display information about places of worship in Fakfak. The method used in this research is a waterfall process model. This application is tested using black box methods and questionnaires. The result reveals that an Android-based application of the Geographic Information System for Places of Worship in Fakfak Regency can help to make it easier for tourists and the Fakfak community to find and obtain information related to places of worship in Fakfak. The results of the black box test state that the functions of the application are running well. The questionnaire test gave results from questions filled out by 20 respondents who stated that the application of the Geographic Information System for Places of Worship was suitable to use by the Fakfak community in obtaining information about places of worship and information on religious history and making it easier for users to find the location of the worship places they wanted to visit.